Psoralen alleviates high glucose-induced HK-2 cell injury by inhibition of Smad 2 signaling via upregulation of microRNA 874 - Yongtao Lin; Lili Zhong; Hailun Li; Yong Xu; Xiang Li; Donghui Zheng (BMC, 2020)
Abstract Background Diabetic nephropathy (DN) causes the vast proportion of excess mortality for patients with diabetes. Novel therapeutic approaches slowing down its incidence is still lacking. Psoralen is the major active ingredient of Psoralea corylifolia Linn. (PCL), which was used to treat a number of diseases. In this study, we aimed to investigate whether psoralen could alleviate DN using in vitro model. Methods Cell viability assay and immunofluorescence were used to evaluate the effect of psoralen on high glucose (HG)-stimulated human kidney HK-2 cells (48 h). RT-qPCR was used to detect the expressions of miRNA in cells. Cell transfection, apoptosis assay, inflammatory cytokines detection and Western blot were further performed to explore the underlying molecular mechanisms. Results HG-induced toxicity of HK-2 cells was alleviated by psoralen. Meanwhile, the secretion of inflammatory cytokines and extracellular matrix (ECM) accumulation induced by HG in HK-2 cells were also decreased by psoralen. In addition, the expression of miR-874 in HK-2 cells was significantly upregulated by psoralen. Western blot assays indicated that psoralen could reverse HG-induced increase of TLR-4/NF-κB and Smad2 via upregulation of miR-874. Conclusion This study demonstrated that psoralen could significantly alleviate HG-induced HK-2 cell injury via upregulation of miR-874. In addition, HG-induced increase of TLR-4/NF-κB and Smad2 was revered by psoralen. Therefore, psoralen might serve as an agent for the treatment of DN.